The influence of organic carbon on the toxicity of sediment-associated dinonylnaphthalene sulfonic acids to the benthic invertebrates Tubifex tubifex and Hyalella azteca. (December 2020) - Matten, K.J.; Bartlett, A.J.; Milani, D.; Gillis, P.L.; Parrott, J.L.; Toito, J.; Balakrishnan, V.K.; Prosser, R.S.
Abstract: Naphthalene sulfonic acids (NSAs) are used extensively in industrial applications as dispersants in dyes, rubbers, and pesticides, and as anti-corrosive agents in coatings, gels, and sealants. This study examined the toxicity of three NSA congeners, barium dinonylnaphthalene sulfonate (BaDNS), calcium dinonylnaphthalene sulfonate (CaDNS), and dinonylnaphthalene disulfonic acid (DNDS), to two benthic species, Tubifex tubifex and Hyalella azteca . Two substrates with different levels of organic carbon (sediment [2%] and sand [0%]) were used in toxicity tests. Juvenile production was the most sensitive endpoint for T. tubifex : the 28-d EC50s were <18.2, 22.2, and 64.0 μg/g dw in sand and 281.3, 361.6, and 218.9 μg/g dw in sediment for BaDNS, CaDNS, and DNDS, respectively. The 28-d LC50s for H. azteca were similar among compounds: 115.3, 82.1, and 49.0 μg/g dry weight (dw) in sand, and 627.3, 757.9, and >188.5 μg/g dw in sediment, for BaDNS, CaDNS, and DNDS, respectively. However, when LC50s were estimated based on concentrations of NSAs measured in overlying water (which can be an important route of exposure for H. azteca ), BaDNS and CaDNS were 3–4 orders of magnitude more toxic than DNDS. The NSAs examined were >3-fold more toxic when present in substrates with no organic carbon (e.g., sand) for all H. azteca endpoints where LC/EC50s could be calculated and for sublethal endpoints for T. tubifex . The organic carbon content of the sediment appears to have acted as a sink and reduced NSA toxicity by decreasing bioavailability. Environmental sediment samples were collected from 12 river sites across southern Ontario. The maximum concentration of CaDNS observed in sediment collected from this region was 2.8 μg/g dw in sediment with 2% organic carbon; 100-fold lower than the lowest EC10 in the current study. Graphical abstract: Image 1 Highlights: Naphthalene sulfonates are additives in a wide range of industrial products. Organic carbon content significantly influences toxicity of naphthalene sulfonates. Sulfonate salts were more toxic than sulfonic acid to benthic invertebrates.